El concepto de persona. Una relectura de la propuesta de P. F. Strawson - Muñoz Sánchez, María Teresa (Revista de Filosofía, 2008)
This article offers a review of the chapter dedicated by Strawson to the concept of a person in Individuals. Characteristics given to the concept of person by Strawson are criticized by Bernard Williams. What I set out to show is that this criticism can be answered by reviewing: a) how Strawson understands that the concept of a person is primitive, b) what are the implications of affirming the primitiveness of such concept, and, mainly c) what this philosopher understands by referring.